2022
DOI: 10.1136/bmjopen-2021-060023
|View full text |Cite
|
Sign up to set email alerts
|

Medico-legal litigation of UK physiotherapists in relation to cauda equina syndrome: a multimethods study

Abstract: ObjectiveThe aim was to investigate the extent of cauda equina syndrome (CES) litigation and explore the process of medico-legal litigation in relation to physiotherapy in the UK.DesignA multimethods inquiry that followed on from a previously conducted scoping literature review was undertaken to address the aim. This included freedom of information requests and direct communication with relevant stakeholders and organisations.ResultsA total of 2496 CES claims were found in the UK between 2012 and 2020. 51 of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…Participants were eligible if they were a qualified physiotherapist who had been involved in CES litigation in the UK. However, to gain a holistic understanding of the phenomenon of interest, previous research indicated the need to understand the experience of UK physiotherapists at risk of CES litigation i.e., those working in advanced roles [ 7 , 8 ]. Furthermore, for context and to aid understanding of the issue, we also needed to speak to a range of stakeholders, who included:…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Participants were eligible if they were a qualified physiotherapist who had been involved in CES litigation in the UK. However, to gain a holistic understanding of the phenomenon of interest, previous research indicated the need to understand the experience of UK physiotherapists at risk of CES litigation i.e., those working in advanced roles [ 7 , 8 ]. Furthermore, for context and to aid understanding of the issue, we also needed to speak to a range of stakeholders, who included:…”
Section: Methodsmentioning
confidence: 99%
“…An interview topic guide ( S1 File ) was used to guide the interview to provide further consistency and to direct the interview by providing a priori topics to be explored in relation to the aim of the study, whilst allowing sufficient flexibility to explore new and unanticipated issues. The interview guide was developed from a review of the literature [ 7 , 8 ] and was refined following piloting and critical discussion with the research team and a patient and public involvement group (PPI). The PPI group included three people living with CES and a physiotherapist who had been involved in a CES litigation case.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations